A dataset on the sensory and affective perception of Bordeaux and Rioja red wines collected from French and Spanish consumers at home and international wine students in the lab - Michel Visalli; Magalie Dubois; Pascal Schlich; François Ric; Jean-Marie Cardebat; Nikolaos Georgantzis (Data in Brief, 2023)
This article describes a dataset providing temporal sensory descriptions and affective answers for red wines: two Bordeaux and two Riojas. The wines were tasted at home by French (FR, n=106) and Spanish (SP, n=98) consumers and in the lab by wine students (WC, n=47). Standardized information was displayed on the samples (country and region of origin, name, producer, vintage, alcohol content). The FR and SP panels were split into three groups, the first having no rating information, the second having expert rating information (based on Wine Advocate ratings), and the third having consumer rating information (based on online Vivino reviews). The participants first rated their expected liking for the four wines. Then, for each wine sample, they had (in order) to taste the sample while being video recorded, rate their liking, temporally describe the sequence of sensations they perceived using Free-Comment Attack-Evolution-Finish, answer several questions about familiarity and quality perception, and declare their willingness to pay (reserve price). Then, they had to rank the four wines according to their quality. General questions about wine involvement, subjective wine knowledge, valuation behaviour, purchasing, and consumption patterns were asked. Finally, an auction was resolved: participants declaring a reserve price greater than the drawn price won a bottle. The data were used to assess the influence of culture and expertise on temporal sensory evaluations in an article entitled “Using Free-Comment to investigate expertise and cultural differences in wine sensory description”. The data can be reused by researchers interested in studying the impact of external information on preferences and choices or investigating the sensory drivers of liking.